Se essa rua fosse minha: Construção de uma Pedagogia da Rua dialógica nas aulas de educação física - Mattos, Kelly Botelho Assis (Universidade Federal de São Carlos, 2024)
This research proposal stems from our concerns regarding the high dropout rate of Physical Education classes among students in the final years of Elementary School. Based on these concerns, we set out to reflect on the pedagogical potential of rescuing and building a dialogical approach to collective sports, through the principles of the Pedagogy of the Street. This "street" is understood both metaphorically and literally. The research question is presented as follows: "What educational processes emerge from an intervention based on the pedagogy of the street?". The main objective of this research is to analyze the educational processes that emerge from the implementation of a didactic unit guided by the Pedagogy of the Street in a dialogical perspective with an 8th grade class of Elementary School. This is a qualitative research of the strategic action-research type, developed by the teacher-researcher herself, through the implementation of a didactic unit composed of nine sessions with the participating class. The instrument used for data production was the Class Diary, with the sources for the records being participant observation and audio and video recordings produced during the sessions, including conversation circles. The next step, data analysis, was carried out through coding categories, in three moments: organization and reading of the collected documents, coding and finally categorization. The results and their analysis are organized into two main Freire’s theoretical categories; Limit Situations and Viable Unprecedented, and their respective subcategories, being Banking Conception, Gender Prejudices and Competitiveness for the Limit Situations category and Dialogicity and Perceived Highlighted for the Viable Unprecedented category. In the first reflections, it was possible to verify that the banking conception of education showed itself as a limiting factor for the participating class to experience humanizing educational processes; gender oppressions appear as one of the biggest obstacles in the expansion of experiences, as well as the exacerbated competitiveness imposed, especially by the most experienced students. In the second category, we highlight that the understanding of educational processes for an engaged participation strengthened the class's bonds of understanding. We consider that Dialogicity played a fundamental role in the educational processes that emerged from the proposed research.
If this street were mine: Building a dialogical Street Pedagogyin physical education classes
Keywords: Educação física escolar; Pedagogia da Rua; Dialogicidade; Physical education; Pedagogy of the Street; Dialogicity; CIENCIAS HUMANAS::EDUCACAO::TOPICOS ESPECIFICOS DE EDUCACAO